Community based quality monitoring (CBQM) study of key harm reduction services for people who use drugs in Cambodia, Indonesia, Nepal and Vietnam: country report Nepal. - Poudel,Prabhu Raj (2019)
ABSTRACT: Context: This study comes in the context of a multi-country grant from the Global Fund to ANPUD and other three regional networks. One of the components of the grant is to conduct a study to monitor the quality of services related to Needle Syringe Exchange Programming (NSP), Opioid Substitution Therapy (OST) and linkage to health care for people who inject drugs (PWID) in Cambodia, Indonesia, Nepal and Vietnam. In this backdrop, the report comes as the country report of Nepal, as a part and partial of the regional study, conducted by ANPUD along with Recovering Nepal, the national network of People who Use Drugs (PUD) in Nepal, with the financial support of a regional grant from the Global Fund, namely: Key Population Research Advocacy Project. Objective: Key specific objective of this study is to improve understanding of the perceived quality of harm reduction services among PWID in Cambodia, Indonesia, Nepal and Vietnam. The broader objective of this study is to build evidence for advocacy for improved quality of Harm Reduction, HIV, HBC, HCV prevention and care services to PWID in Cambodia, Indonesia, Nepal and Vietnam. Research design: A mixed methods research entailing of community survey (CS) using structured interview and focus group discussion (FGD) among service users of NSEP and OST and key informant interview (KII) among service providers in Kathmandu and Pokhara cities of Nepal. Results: It was found that 92% of service users of NSEP were either very satisfied or satisfied with the overall quality of survey while around 7% were neutral to the overall quality. Less than one percent were found dissatisfied with the overall quality of NSEP. In the context of OST, more than a half of service users (64.10%) agreed - among which a quarter of respondents (25.60%) strongly agreed and more than two-third (38.50%) agreed; that OST services they had been receiving was perfect. In contrast only 17.10 % either strongly disagreed or disagreed that OST services they had been receiving was perfect. Key Words: Harm Reduction, People Who inject drugs, Needle Syringe Exchange Program (NSP), Opioid Substitution Therapy (OST), HIV